The Effect of The Problem Based Learning Model on The Analytical Thinking Skills of Elementary School Students - Marlina, Leni; Diana, Nanang; Haryadi, Didit; Zulkifli, Zulkifli; Komalasari, Desy Ningsih (Journal of Educational Sciences, 2025)
Analytical thinking skills are a form of higher-order thinking that is important to develop from elementary school, especially through Indonesian language learning. This study aims to determine the effect of the Problem-Based Learning (PBL) model on the analytical thinking skills of fourth-grade elementary school students on the theme “The Uniqueness of My Hometown.” The research method used is quantitative with a quasi-experimental design of the one-group pretest-posttest type. The research subjects consisted of 20 fourth-grade students at SDN O’o Donggo. The instrument used was an essay test consisting of 7 questions based on indicators of analytical thinking. The data were analyzed using a paired sample t-test. The results showed a significant increase in the average scores between the pretest and posttest (p < 0.05). The most improved indicators were the ability to construct arguments and draw conclusions. It is concluded that the PBL model is effective in enhancing students’ analytical thinking skills through contextual problem-solving activities, discussions, and group work. This model is recommended for use in Indonesian language learning to make the process more active and meaningful.